2018
DOI: 10.5897/ajar2018.13152
|View full text |Cite
|
Sign up to set email alerts
|

Plant cover management and nitrogen fertilization in maize crop in a dystrophic red Latosol Brazilian Cerrado (Savannah)

Abstract: An experiment was conducted in the agricultural year 2014/2015, aiming to evaluate the management of anticipated nitrogen fertilization, applied with a slow-release source in maize crop with two plant covers, in a Dystrophic Red Latosol. Matching the Oxisols in Soil Taxonomy and Ferralsols FAO/United States WRB (Unesco soil classification and the World Reference Base for Soil Resources. Pennisetum glaucus (Pennisetum glaucum (L.) R. Br.) and Raphanus sativus (Raphanus sativus L.) were used as green cover, keep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…The critical examination of these trials and examination of the growth curve indicated that 583g of N/plant, 271g of P/plant and 400g of K/plant are optimum for guava. Jose et al [4] conducted a trial to assess the different fertilizer amounts on four-year-old guava variety Paluma under a micro irrigation system with 6m x 5 m spacing, under a tropical semi-arid climate in Brazil. Application of 600g of nitrogen and 300g of potassium resulted in 7.5 tonnes/ha yield of the crop and an average fruit weight of 200g.…”
Section: Introductionmentioning
confidence: 99%
“…The critical examination of these trials and examination of the growth curve indicated that 583g of N/plant, 271g of P/plant and 400g of K/plant are optimum for guava. Jose et al [4] conducted a trial to assess the different fertilizer amounts on four-year-old guava variety Paluma under a micro irrigation system with 6m x 5 m spacing, under a tropical semi-arid climate in Brazil. Application of 600g of nitrogen and 300g of potassium resulted in 7.5 tonnes/ha yield of the crop and an average fruit weight of 200g.…”
Section: Introductionmentioning
confidence: 99%